DEBT AND AGENCY CONFLICT IN INDONESIAN MANUFACTURING FIRMS - Hendra Wijaya; Rr. Puruwita Wardani (Jurnal Keuangan dan Perbankan, 2017)
Companies in Indonesia have shareholders who are not dispersed or in other words theownership is only held by one majority shareholder. This study examined the effects ofinvestment decision on the firm value and the debt moderation on the effects of investmentdecisions on firm value. Debt moderation was used to test the agency conflict of debtuse on investment decision. The company samples in this research were 90 companies.This research was conducted by using panel data regression with moderation. This studyfound that investment decision had a positive effect on firm value and the use of higherdebt could lower the positive effect of investment decision on firm value.